Crafting the culture and history of French chocolate - Terrio, Susan J. (Susan Jane), 1950- (University of California Press, 2000)
This absorbing narrative follows the craft community of French chocolatiers--members of a tiny group experiencing intensive international competition--as they struggle to ensure the survival of their businesses. Susan J. Terrio moves easily among ethnography, history, theory, and vignette, telling a story that challenges conventional views of craft work, associational forms, and training models in late capitalism.